2021
DOI: 10.3897/aiep.51.70223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic androgen (17α-methyltestosterone) and estrogen (17β-estradiol) on growth and skin coloration in emperor red cichlid, Aulonocara nyassae (Actinopterygii: Cichliformes: Cichlidae)

Abstract: In recent years, the use of anabolic steroids in the coloration and growth of fishes, especially ornamental ones, has attracted great interest. In the ornamental fish industry, it is economically advantageous to produce some species with high commercial value and higher demand, depending on size, color, and sex. Therefore, the most commonly used steroids in this study—i.e., 17α-MT and 17β-Es (E2)—were added to the diet of emperor red cichlid, Aulonocara nyassae Regan, 1922, which has not been previously hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The survival rate of tilapia in this experiment is consistent to that of tilapia treated with oral administration method for 21 days of authors such as Tu (2006) (69.5 -83.4%), Jensi et al (2016) (87.33 -95.00%) and Alam et al (2023) (81.3 -92.0%). In addition, this result is similar to the survival rate of other fish when treated with feeding methods such as Aulonocara nyassae (62.2 -93.3%) (Karslı, 2021) and Clarias gariepinus (81.1 -92.2%) (Alam et al, 2023).…”
Section: Discussionsupporting
confidence: 80%
“…The survival rate of tilapia in this experiment is consistent to that of tilapia treated with oral administration method for 21 days of authors such as Tu (2006) (69.5 -83.4%), Jensi et al (2016) (87.33 -95.00%) and Alam et al (2023) (81.3 -92.0%). In addition, this result is similar to the survival rate of other fish when treated with feeding methods such as Aulonocara nyassae (62.2 -93.3%) (Karslı, 2021) and Clarias gariepinus (81.1 -92.2%) (Alam et al, 2023).…”
Section: Discussionsupporting
confidence: 80%
“…The study revealed the stimulatory effect of E 2 on IGFs, while MT exhibited an inhibitory effect [ 18 , 47 ]. In common carp [ 66 ], the results showed that E 2 and MT significantly affected IGF2 expression, with E 2 increasing IGF2 mRNA levels and MT decreasing IGF2 mRNA levels [ 66 , 68 ]. The study concluded that E 2 and MT had opposite effects on IGF2 mRNA expression in the carp and that E 2 had a more pronounced effect than MT [ 66 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In common carp [ 66 ], the results showed that E 2 and MT significantly affected IGF2 expression, with E 2 increasing IGF2 mRNA levels and MT decreasing IGF2 mRNA levels [ 66 , 68 ]. The study concluded that E 2 and MT had opposite effects on IGF2 mRNA expression in the carp and that E 2 had a more pronounced effect than MT [ 66 , 68 ]. Another study on the Coho salmon showed that both E 2 and MT had a positive effect on IGF2 mRNA expression [ 69 ].…”
Section: Discussionmentioning
confidence: 99%